Pengabdian Kepada Masyarakat Anggota Pemberdayaan Kesejahteraan Keluarga di Kelurahan Cinere dan Kelurahan Gandul Depok Jawa Barat - Didi Zainuddin; Elfitria Wiratmani; Ridwan Usman (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
PKM members of PKK in Cinere and Gandul sub-districts of Depok West Java were conducted by Didi Zainuddin, Elfitria Wiratmani, Ridwan Usman from the Department of Industrial Engineering, Faculty of Engineering and Computer Science, PT Indraprasta University. Jakarta tel (021) 7818718-78835253 with Email: didiza.gadept@gmail.com1, elfitriaw@gmail.com2, ridwansmn@gmail.com Considering the current very tight competition and market conditions in the field of designing new products is something that must be done by the company to maintain its existence. Through the PKK organization we introduce members' creativity development skills, especially how to package products to be sold, especially traditional foods or regional specialties. The problem faced by the PKK members of Cinere and Jakarta City barren is the lack of packaging of cakes, fried foods and snacks, so that the effect on the lack of maximum sales. The implementation of this community service activity is carried out through the observation stage of determining the material needed from product development and marketing itself. Community service with PKK cinere and barren members conducts workshops on understanding and product development materials in packaging and marketing. with the large number of participants present from surrounding residents and members of the PKK Organization activities adding skills, knowledge and results are very useful especially how to present products that appeal to consumers according to their wants and needs.